Profil Pendidikan Berasrama pada Sekolah dan Madrasah Negeri - Wahyu Fajar Faadhilah; Asep Dudi Suhardini; Fitroh Hayati (Bandung Conference Series: Islamic Education, 2022)
Abstract. The background of this research is that there are public schools in Bandung which have dormitories for SMA Negeri X Cisarua and MA Negeri 1 Bandung, this study aims to determine the profile of boarding education in the Student Development Dormitory of SMA Negeri X Cisarua and Al-Muraby Integrated Islamic Boarding School, MA Negeri 1 City. Bandung, as well as to find out the education system and the comparison of the two schools. The approach used is a qualitative approach with a descriptive analytical research type with a case study method of multi-case type. The results of the research on the profile of boarding education in the Student Development Dormitory of SMA Negeri X Cisarua and the Al-Muraby Integrated Islamic Boarding School MA Negeri 1 Bandung already have their respective standards in accordance with eight National Education Standards covering graduate competency standards, content standards, process standards, educational assessment standards , standards for teaching and educational staff, standards for infrastructure, management standards, and financing standards. The difference between the two institutions based on these eight standards is that the Student Development Dormitory of SMA Negeri X Cisarua is not part of the school because it is directly owned by the West Java Provincial Government, while the Al-Muraby Integrated Islamic Boarding School, MA Negeri 1 Bandung City, becomes a single unit with the madrasa, so that facilities and infrastructure are integrated. And the research findings are that boarding schools are more supportive of religious knowledge, school materials, student independence, and student discipline. Abstrak. Penelitian ini dilatar belakangi oleh terdapat sekolah negeri di Bandung yang memiliki asrama SMA Negeri X Cisarua dan MA Negeri 1 Kota Bandung, penelitian ini bertujuan untuk mengetahui profil pendidikan berasrama di Asrama Bina Siswa SMA Negeri X Cisarua dan Pesantren Terpadu Al-Muraby MA Negeri 1 Kota Bandung, serta untuk mengetahui sistem pendidikan dan perbandingan dari dua sekolah tersebut. Pendekatan yang digunakan adalah pendekatan kualitatif dengan jenis penelitian deskriptif analitik dengan metode studi kasus tipe multi kasus. Hasil penelitian profil pendidikan berasrama di Asrama Bina Siswa SMA Negeri X Cisarua dan Pesantren Terpadu Al-Muraby MA Negeri 1 Kota Bandung sudah memiliki standarnya masing-masing sesuai dengan delapan Standar Nasional Pendidikan meliputi standar kompetensi lulusan, standar isi, standar proses, standar penilaian pendidikan, standar tenaga pendidik dan kependidikan, standar sarana prasarana, standar pengelolaan, dan standar pembiayaan. Perbedaan dua lembaga tersebut berdasarkan delapan standar tadi adalah Asrama Bina Siswa SMA Negeri X Cisarua itu bukan merupakan bagian dari sekolah karena dipegang langsung oleh Pemerintah Provinsi Jawa Barat, sedangkan Pesantren Terpadu Al-Muraby MA Negeri 1 Kota Bandung itu menjadi satu kesatuan dengan madrasah, sehingga sarana dan prasarananyapun menyatu. Dan penemuan penelitian adalah sekolah diasrama itu lebih menunjang ilmu agama, materi-materi di sekolah, kemandirian siswa, dan kedisiplinan siswa.